Management of Rheumatoid Arthritis: Consensus Recommendations From the Turkish League Against Rheumatism - Zafer GÜNENDİ and Salih ÖZGÖÇMEN19 and Mahmut YENER and Birkan SONEL TUR and Aylin REZVANİ and Nurdan PAKER and Neşe ÖLMEZ and Taciser KAYA and Ece KAPTANOĞLU and Cahit KAÇAR and et al. (Archives of Rheumatology, 2011)
Objectives: Taking new developments in the management of rheumatoid arthritis (RA) and the economic conditions of our country into account, the Turkish League Against Rheumatism (TLAR) aimed to develop national treatment recommendations for the management of RA; thus, they consulted with national experts for their opinions. Materials and methods: Eight rheumatologists and 15 physiatrists experienced in the field contributed to the development of the TLAR recommendations for the management of RA. The expert committee planned to develope “Recommendations for the Management of RA in Turkey” based on EULAR 2010 recommendations for the management of RA with synthetic and biological disease-modifying antirheumatic drugs (DMARDs) in light of expert opinions. Following the meeting, a systematic literature review was performed by searching the Medline and Cochrane, Embase, and Turkish Medical Index databases between 2009 and 2010 for pharmacological treatment recommendations and between 2007 and 2010 for non-pharmacological treatment recommendations. This was done in addition to the studies included in the EULAR 2010 recommendations. All articles were examined, their contents were summarized, their levels of evidence were determined, and the Delphi process was initiated. Results: Sixteen general recommendations were listed along with five main principles and one non-pharmacological treatment method. A consensus was reached for all recommendations, and their strength levels were voted upon. Conclusion: Recommendations were formed for the management of RA in Turkey. These national recommendations are intended to guide physical medicine and rehabilitation specialists (physiatrists), rheumatologists, and family physicians and should be regularly updated.